Characterization of a candidate dual AGN. Issue 1 (3rd May 2018) - Lena, D; Panizo-Espinar, G; Jonker, P G; Torres, M A P; Heida, M
Abstract: We present Chandra and optical observations of a candidate dual active galactic nucleus (AGN) discovered serendipitously while searching for recoiling black holes via a cross-correlation between the serendipitous XMM source catalogue (2XMMi) and SDSS-DR7 galaxies with a separation no larger than 10 times the sum of their Petrosian radii. The system has a stellar mass ratio M 1 / M 2 ≈ 0.7. One of the galaxies (Source 1) shows clear evidence for AGN activity in the form of hard X-ray emission and optical emission-line diagnostics typical of AGN ionization. The nucleus of the other galaxy (Source 2) has a soft X-ray spectrum, bluer colours, and optical emission-line ratios dominated by stellar photoionization with a 'composite' signature, which might indicate the presence of a weak AGN. When plotted on a diagram with X-ray luminosity versus [Oiii ] luminosity, both nuclei fall within the locus defined by local Seyfert galaxies. From the optical spectrum, we estimate the electron densities finding n 1 < 27 e − cm −3 and n 2 ≈ 200 e − cm −3 . From a 2D decomposition of the surface brightness distribution, we infer that both galaxies host rotationally supported bulges (Sérsic index <1). While the active nature of Source 1 can be established with confidence, whether the nucleus of Source 2 is active remains a matter of debate. Evidence that a faint AGN might reside in its nucleus is, however, tantalizing.